Oblique Incidence of Seismic Wave Reflecting Two Components of Design Ground Motion - W. J. Cen; X. H. Du; D. J. Li; L. N. Yuan (Shock and Vibration)
The wave field on the artificial boundary was separated into the free field without local topography effect and scattering field induced by local topography effect. The simulation of the free field under obliquely incident waves was conducted. Based on the assumption that the components of design ground motion were treated as the coincidence of oblique P wave and oblique SV wave, the relationship between the oblique input waves and the design ground motion was established in the free field. Further, the contributions to the two components of design ground motion of obliquely incident waves were discussed. The calculation model in time domain was achieved by the combination of the propagation characteristics of obliquely incident waves and the artificial boundary in the free field. The seismic response to the design ground motion was produced on the free surface. The verification of the 2D half-space model under oblique input waves indicated that the wave input method can accurately reflect the design ground motion on the free surface. Application of an earth-rock dam showed that oblique incidence of seismic waves results in significantly different dynamic response compared with the normal incidence. The proposed method can also be employed in the seismic analysis of large span structures with nonuniform ground motion input.